Cyclophosphamide-induced melanonychia - Amirali, Mazhar H; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2019)
A case of drug-induced melanonychia due to cyclophosphamide is described in a patient with lupus nephritis. This resolved completely at 20 weeks after stopping the drug. Clinicians should be aware of the causes of melanonychia, and, if drug-induced melanonychia is suspected, the offending drug should be stopped whenever possible.